2017
DOI: 10.3389/fphar.2017.00368
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Sulfatase Pathway for Local Estrogen Formation in Endometrial Cancer

Abstract: Endometrial cancer (EC) is the most common estrogen-dependent gynecological malignancy in the developed World. To investigate the local formation of estradiol (E2), we first measured the concentrations of the steroid precursor androstenedione (A-dione) and the most potent estrogen, E2, and we evaluated the metabolism of A-dione, estrone-sulfate (E1-S), and estrone (E1) in cancerous and adjacent control endometrium. Furthermore, we studied expression of the key genes for estradiol formation via the aromatase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 44 publications
8
32
0
Order By: Relevance
“…These have been associated with EC and breast cancer progression, supporting the role of bradykinin in tumors originating from steroid sensitive tissues (39,40). Sulfated androgens were also higher in type I EC cases, consistent with the reported implication of sulfated steroids in this histotype (8,(41)(42)(43)(44). Furthermore, our data identified heme as a putative biomarker of type II EC and highlighted modifications in pathways closely related to heme synthesis, namely the tetrahydrofolate-serine/glycine pathway (45).…”
Section: Discussionsupporting
confidence: 84%
“…These have been associated with EC and breast cancer progression, supporting the role of bradykinin in tumors originating from steroid sensitive tissues (39,40). Sulfated androgens were also higher in type I EC cases, consistent with the reported implication of sulfated steroids in this histotype (8,(41)(42)(43)(44). Furthermore, our data identified heme as a putative biomarker of type II EC and highlighted modifications in pathways closely related to heme synthesis, namely the tetrahydrofolate-serine/glycine pathway (45).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, STS can metabolise E1S and E2S sulphate to bioactive E1 and E2 respectively. STS is expressed in normal endometrial tissues and in endometrial cancers [49,50]. STS expression and activity is increased during decidualisation of endometrial stromal cells in vitro consistent with a detectable increase in oestrogens detected in tissue samples recovered during the secretory phase [3,46].…”
Section: Role Of Sulphated Steroids As a Source Of Endometrial Androgsupporting
confidence: 66%
“…Obesity is a known risk factor of EC [4] and this may be partly related to the fact that adipose tissue represents a major source of estrogen synthesis in postmenopausal women, actively converting adrenal and androgen precursors to estrogens resulting in increased serum bioavailable estradiol (E 2 ) [5,6]. Previous work by our group and others has revealed that the potent estrogen E 2 primarily derive from conversion of estrone-sulfate (E 1 -S) in EC tumors rather than aromatization of androgens by the aromatase (CYP19), which has barely detectable expression levels in EC cells [7][8][9][10]. Besides, E 2 and E 1 may be converted into numerous biologically active derivatives with varying mitogenic and genotoxic properties by the action of various cytochrome P450 and catechol-O-methyl transferase enzymes [11].…”
Section: Introductionmentioning
confidence: 99%